Bending fatigue strength of case-carburized spur gears with boss - Imaduddin Helmi, Wan Nordin; Mohd Afendi, Rojan; Salmie Suhana, Che Abdullah; Mohd Hafis, Sulaiman (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.